2017
DOI: 10.4321/s2254-28842017000100009
|View full text |Cite
|
Sign up to set email alerts
|

Factores que influyen en la satisfacción del paciente de diálisis con enfermería

Abstract: Introducción: La satisfacción del paciente con los cuidados enfermeros se ha convertido en un determinante clave de la calidad de la atención sanitaria. Además, esto es especialmente relevante, sobre todo en pacientes crónicos, como es el caso del paciente con enfermedad renal crónica avanzada en hemodiálisis. Objetivo: Analizar los factores que intervienen en la satisfacción de los pacientes en hemodiálisis respecto al personal de enfermería. Metodología: Se ha llevado a cabo un estudio cualitativo, de tipo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Only four studies were directly about cannulation. 8,9,17,18 Other studies were about pain, 26,27 experiences of VA for haemodialysis, 14,[28][29][30][31][32][33] experiences of in-centre and home haemodialysis [34][35][36][37][38][39][40][41][42][43][44][45][46] and research priority setting. 47 Studies were conducted across five continents, but despite this diversity in study location themes extracted did not seem to vary due to culture, with the exception of one study, which developed themes linked to religion in a Thai culture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only four studies were directly about cannulation. 8,9,17,18 Other studies were about pain, 26,27 experiences of VA for haemodialysis, 14,[28][29][30][31][32][33] experiences of in-centre and home haemodialysis [34][35][36][37][38][39][40][41][42][43][44][45][46] and research priority setting. 47 Studies were conducted across five continents, but despite this diversity in study location themes extracted did not seem to vary due to culture, with the exception of one study, which developed themes linked to religion in a Thai culture.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of cannulation is not only evident in studies that specifically explore cannulation, but is also highlighted in studies that explore experiences of VA 14,[28][29][30][31][32][33] and haemodialysis. [34][35][36][37][38][39][40][41][42][43][44][45][46] Casey et al's 7 systematic review identified 'fear of cannulation' as part of patients' experiences of VA for haemodialysis and a key area of concern. Whilst studies have found there was better patient satisfaction with AV fistulae in comparison to AV grafts and CVCs, patients with AV access were more likely to be bothered by symptoms associated with cannulation, namely the appearance of their access, pain, bruising and swelling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas satisfaction patient according to [18] is something situation Where client and family consider costs incurred in accordance with quality service received and level progress condition his health. System service given health For patient at first always oriented to disease but moment This various effort has done in enhancement service health besides That public general has more interested about enhancement service that is , awareness public the influenced by letters newspapers , magazines , electronic media , and other communication media as well as by their existence debates transparent politics , with awareness public the so they start have great faith that health and services health is right basic and not just facility For certain group of people [17].…”
Section: Introductionmentioning
confidence: 99%